2022
DOI: 10.1111/ddg.14796
|View full text |Cite
|
Sign up to set email alerts
|

Hidradenitis suppurativa‐related expenditure, a call for awareness: systematic review of literature

Abstract: A systematic literature search was conducted to detect studies documenting the economic burden (direct and indirect) associated with HS. Studies were considered eligible for inclusion, as long as they contained financial data regarding any domain of healthcare or other expenditure incurred by this disease and/or documented the impact of HS on work, income and personal economic growth (indirect disease cost).No restrictions were imposed on study design, currency used, language and year of publication. Informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
6

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 37 publications
1
8
0
6
Order By: Relevance
“…29 For those with limited health insurance coverage or those who cannot afford routine care or targeted therapies such as adalimumab, their disease may progress, requiring repeat procedures that confer even greater financial cost. 30,31 In this study we also found that a concomitant psychiatric disease in patients with HS was not associated with longer hospital LOS. Regardless, prolonged hospital stays can lead to This article is protected by copyright.…”
Section: Accepted Manuscriptsupporting
confidence: 63%
“…29 For those with limited health insurance coverage or those who cannot afford routine care or targeted therapies such as adalimumab, their disease may progress, requiring repeat procedures that confer even greater financial cost. 30,31 In this study we also found that a concomitant psychiatric disease in patients with HS was not associated with longer hospital LOS. Regardless, prolonged hospital stays can lead to This article is protected by copyright.…”
Section: Accepted Manuscriptsupporting
confidence: 63%
“…The results indicate that screening for follicular occlusion disorders should be performed in FD patients and that in cases of comorbid HS, a more aggressive treatment approach should be considered. 39 Other comorbid diseases, such as metabolic syndrome or its components, atopy, and others, occurred at comparable rates to the general population of similar ages. [40][41][42][43] Similar to previous studies, no link to immunodeficiency disorders was discovered, and the majority of cases were sporadic.…”
Section: Discussionmentioning
confidence: 94%
“…Though other follicular occlusion triad disorders were found, HS was the most significantly associated finding with FD disease severity. The results indicate that screening for follicular occlusion disorders should be performed in FD patients and that in cases of comorbid HS, a more aggressive treatment approach should be considered 39 …”
Section: Discussionmentioning
confidence: 96%
“…Obwohl andere Erkrankungen der Trias der follikulären Okklusion identifiziert wurden, war HS der Befund mit der am deutlichsten signifikanten Assoziation zum Schweregrad der FD. Dies impliziert, dass bei FD‐Patienten ein Screening auf Erkrankungen mit follikulärer Okklusion durchgeführt und bei komorbider HS ein aggressiverer Behandlungsansatz erwogen werden sollte 39 …”
Section: Diskussionunclassified
“…Dies impliziert, dass bei FD-Patienten ein Screening auf Erkrankungen mit follikulärer Okklusion durchgeführt und bei komorbider HS ein aggressiverer Behandlungsansatz erwogen werden sollte. 39 Andere Begleiterkrankungen, wie das metabolische Syndrom und seine Komponenten, Atopie und andere, traten in vergleichbaren Raten wie bei der Allgemeinbevölkerung ähnlichen Alters auf. [40][41][42][43] Wie auch in früheren Studien wurde kein Zusammenhang mit Immundefektkrankheiten festgestellt und die meisten Fälle waren sporadisch.…”
Section: Diskussionunclassified